Comparative Analysis of Podocyte Foot Process Morphology in Three Species by 3D Super-Resolution Microscopy - Artelt, Nadine; Siegerist, Florian; Ritter, Alina M.; Grisk, Olaf; Schlüter, Rabea; Endlich, Karlhans; Endlich, Nicole (Frontiers in Medicine, 2018)
Since the size selectivity of the filtration barrier and kidney function are highly dependent on podocyte foot process morphology, visualization of foot processes is important. However, the size of foot processes is below the optical resolution of light microscopy. Therefore, electron microcopy has been indispensable to detect changes in foot process morphology so far, but it is a sophisticated and time-consuming technique. Recently, our group has shown that 3D structured illumination microscopy (3D-SIM), a super-resolution microscopy technique, can visualize individual foot processes in human biopsies. Moreover, we have developed a software-based approach to directly quantify the structure of podocyte foot processes named Podocyte Exact Morphology Measurement Procedure (PEMP). As shown in patients suffering from minimal change disease, PEMP allows the quantification of changes of the foot process morphology by measuring the filtration slit density (FSD). Since rodents are frequently used in basic research, we have applied PEMP to quantify foot processes of mice and rats. Comparative analysis of nephrin-stained kidneys from humans, rats and mice showed significant differences of the FSD. The highest FSD was measured in mice (3.106±0.024 µm-1 (mean±SD)) followed by rats (3.364±0.049 µm-1) and humans (3.829±0.032 µm-1). To demonstrate that PEMP can be used to determine foot process morphology also in affected animals, we measured the FSD in palladin-knockout mice on a 129S1 genetic background compared to wild-type littermates. Taken together, we established a method for the quick and exact quantification of podocyte foot process morphology which can be applied to diagnosis and basic research.